The influence of sprinting speed test and kinematic parameters test on results of 100m dash race particular segments sprinting - Babic, V.; Blazevic, I. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Sprinting speed has certain dynamics which is constantly changing throughout the sprint race phases, whereas the sprint time is the consequence of the optimal coherence of all of these phases. Different qualities attribute differently to sprint race result; reaction time with 1%, the speed of start blocks push-off with 5%, start acceleration with 64%, maximal speed maintainance with 18%, and the ability to resist speed decline in deceleration phase with 12%. The aim of the present research was to investigate the relations of two variables of specific motor tests and eight variables of kinematic parameters with four variables of sprinting dynamics in 100m sprint race. Methods: Participants in this study were 133 male students (aged 21.7 ± 1.08; BH 180.8 ± 6.98 cm; BW 76.6 ± 7.62 kg). For all variables the basic descriptive parameters were computed. Relations of variable 20m sprinting from crouch start (sprinting speed in acceleration phase) and variable 20m sprinting from flying start (sprinting speed in maximum speed phase), as well as their kinematic parameters: average stride frequency, average stride length, foot-ground contact average duration, flight average duration in different phases of 100m sprint (0-30m; 30-60m; 60-80m; 80-100m) were determined using regression analysis. Results & Discussion: Tests of specific motor abilities and kinematic parameters at different segments of 100 race explained 50%-63% of overall 100m sprint results. The multiple correlation ceofficients were from 0,71 to 0,79 with p value of 0,01. The results showed the dominance of maximal sprinting speed influence in all 100m sprint race segments. 20m sprint from flying start is an indicator of quality and efficiency of sprinting motorics. 20m sprint from crouch start, the test used to asses quality of start acceleration, showed to be statistically significant only in start acceleration segment of a race. Sprinting technique kinematic parameters were statistically significant for prediction of all criterion variables of different segments of sprint race (0-30, 30-60, 60-80, 80-100m). In start acceleration segment (0-30m), statistically significant values were obtained for: stride length (for both 20m sprinting tests), whereas in all other sprint race segments (30-60m, 60-80m, 80-100m), statistically significant values were obtained for stride length and stride frequency from 20m sprint flying start test. No other variables showed to be statistically significant although it was expected that foot-ground contact average duration, as an integral indicator of maximal sprinting speed, would have better predictive values. However, this variable was not statistically significant for this population sample.